2019
DOI: 10.5114/jcb.2019.90478
|View full text |Cite
|
Sign up to set email alerts
|

High precision radiotherapy including intensity-modulated radiation therapy and pulsed-dose-rate brachytherapy for cervical cancer: a retrospective monoinstitutional study

Abstract: To analyse the survival outcomes and toxicity profile of patients treated with pulsed-dose-rate (PDR) brachytherapy (BT) after intensity-modulated radiation therapy (IMRT) for uterine cervical cancer in a single institution. Material and methods: Between March 2011 and December 2014, 50 patients with histologically proven stages IB1-IVB cervical cancer were treated with IMRT followed by PDR-BT boost. Radiation treatment consisted of IMRT to pelvic with or without paraaortic lymph nodes to a total dose of 45-50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Compared with surgical treatment, radiotherapy is non-invasive and patients have fewer adverse effects in the intensity-modulated radiation therapy era. [22][23][24][25][26] This may be the reason why the proportion of radiotherapy has increased in recent years in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with surgical treatment, radiotherapy is non-invasive and patients have fewer adverse effects in the intensity-modulated radiation therapy era. [22][23][24][25][26] This may be the reason why the proportion of radiotherapy has increased in recent years in this population.…”
Section: Discussionmentioning
confidence: 99%
“…For Stage IVB cervical cancer, the main purpose of systemic therapy and local therapy is to prolong survival and improve the quality of life of patients. Compared with surgical treatment, radiotherapy is non‐invasive and patients have fewer adverse effects in the intensity‐modulated radiation therapy era 22–26 . This may be the reason why the proportion of radiotherapy has increased in recent years in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Endo/interstitial BT is recommended as a definitive treatment for cervical cancer, as it can deliver high-dose radiation to the tumor while limiting the irradiation of adjacent organs. A population-based analysis revealed that BT use is independently associated with a significantly higher OS, whilst patients unfit for BT are at higher risk of local recurrence (1,3,9,34).…”
Section: Discussionmentioning
confidence: 99%